The Effectiveness of Outbound Games to Improve Gross Motor Skills and Courage of Children Aged 5-6 Years - Pangestu, Akhmadi Putro Aji; Prasetyo, Iis; Munir, Ali (JETL (Journal of Education, Teaching and Learning), 2024)
Outbound is a training and recreation activity carried out in the field or in the open consisting of various games and challenges, and each game has certain goals. Outbound games are a physical game model that can be used by educators to improve gross motor skills and early childhood courage. This study aims to find out: (1) the effectiveness of Outbound games on improving gross motor development in children aged 5-6 years; (2) the effectiveness of outbound games on increasing courage in children aged 5-6 years. The type of research used in this study is quasi-experimental research with a quantitative approach. In this quasi-experimental research using one group Pretest-postest design, namely by providing outbound play activities to determine gross motor skills and children's courage in completing activities. The population in this study is early childhood in TK Negeri Pembina Tasikmadu Karanganyar with a total of 50 children. The sample in this study was children aged 5-6 years in TK Negeri Pembina Tasikmadu Karanganyar totaling 30 children. The sampling technique used is convenian sampling, selection of samples that are appropriate to the age of the child to be studied. The instrument used is to measure children's gross motor skills and courage through outbound game activities. The data analysis technique used is SPSS 25. The results showed that: (1) Outbound games have high effectiveness against increasing gross motor development in children aged 5-6 years, as evidenced by n-gain values of 0.76. (2) Outbound games have high effectiveness against increasing courage in children aged 5-6 years high, as evidenced by n-gain values of 0.90. So from the results of the study, it can be concluded that outbound game activities have a significant impact and have a high effectiveness value on gross motor skills and courage of children aged 5-6 years